The impact that inaccurate credit information has on the key functions within the Credit Department of a Telecommunications company - Govender, Vaneetha (University of the Free State, 2018)
Introduction: The research study explores the impact that the quality of data that is received from the credit bureaux has on the key functions within the credit departments of the three major telecommunication companies in South Africa; that is, Vodacom, MTN and Cell C. This includes a focus on the effectiveness of credit management information used in the credit assessment process that is procured from the major credit bureaux in South Africa. Moreover, a risk framework and its pertinent components are explored in the research regarding the products, processes and interventions that are utilised by telecommunication credit departments when making a credit decision. The overall aim of this study is to ascertain if these actions are robust enough to sustain the business performance or do they need to be refined to optimise the functioning of the credit risk portfolio of the business. Problem statement: The problem is that the data of applicants/customers utilised by the telecommunications companies obtained from the credit bureaux as part of credit decision making, may not be of the standard of quality expected by the credit team in support of sustainable credit performance of the organisation. If the problem is not addressed, the impact thereof is twofold. Firstly, it could result in potential loss of income for the company that could be detrimental to both its bad debt ratios and its credit reputation. Secondly, the impact on the individual consumer is also of concern, as the consumer could find themselves in a debt cycle that will take years to overcome; and the result is further the degradation of consumer well-being and ultimately the state of the economy.
Dissertation (MBA (Business Administration))--University of the Free State, 2018